The Hydrolysis of Carbonyl Sulfide at Low Temperature: A Review. (15th July 2013) - Zhao, Shunzheng; Yi, Honghong; Tang, Xiaolong; Jiang, Shanxue; Gao, Fengyu; Zhang, Bowen; Zuo, Yanran; Wang, Zhixiang
Abstract : Catalytic hydrolysis technology of carbonyl sulfide (COS) at low temperature was reviewed, including the development of catalysts, reaction kinetics, and reaction mechanism of COS hydrolysis. It was indicated that the catalysts are mainly involved metal oxide and activated carbon. The active ingredients which can load on COS hydrolysis catalyst include alkali metal, alkaline earth metal, transition metal oxides, rare earth metal oxides, mixed metal oxides, and nanometal oxides. The catalytic hydrolysis of COS is a first-order reaction with respect to carbonyl sulfide, while the reaction order of water changes as the reaction conditions change. The controlling steps are also different because the reaction conditions such as concentration of carbonyl sulfide, reaction temperature, water-air ratio, and reaction atmosphere are different. The hydrolysis of carbonyl sulfide is base-catalyzed reaction, and the force of the base site has an important effect on the hydrolysis of carbonyl sulfide.